Microstructure and phase composition of bronze Montefortino helmets discovered Mediterranean seabed to explain an unusual corrosion - Francesco Armetta (Nature Portfolio, 2021)
Abstract Two Monterfortino helmets, recovered in the Mediterranean seabed, show unusual features with respect to the more common helmets of the same period and found in underwater environments. Hence, they were investigated by a multi-analytical approach, which allowed us to identify the compounds constituting the helmets and to make some considerations about their metallurgy, although all the metal was converted to degradation products. The helmets, originally made in bronze, have maintained their original shape because of copper sulphides formation. The observed differences in composition between the two helmets were attributed to the position modification, of one of them, into the seabed along centuries. For the first time, a microstructural investigation permits to reconstruct the history of the aging processes involved in the total oxidation of roman bronze helmet metal.